Mechanistic Insight into the Photoinduced Damage of an Unnatural Base Pair. Issue 53 (28th July 2022) - Huo, Bianbian; Zhang, Xiguang; Wang, Chao; Wang, Honglei; Zhu, Gongming; Zhu, Wuyuan; Zhu, Anlian; Mei, Hui; Li, Lingjun
Abstract: Chemical‐ and photostability of unnatural base pairs (UBPs) are important to maintain the genetic code integrity, and critical for developing healthy semisynthetic organisms. As reported, dTPT3 was less stable upon irradiation, and thus might act as a pervasive photosensitizer to induce oxidative damage within DNA, causing harm to living semi‐synthetic organisms when exposed to UVA radiation. However, there was no knowledge about molecular‐level understanding of this damage process. In this paper, we not only identified four photoproducts of dTPT3, including desulfur‐dTPT3 (dTPT3 H ), TPT3 sulphinate (TPT3 SO2 ), TPT3 sulphonate (TPT3 SO3 ) and TPT3‐thioTPT3 (TPT3 S TPT3), but also established a Type II photosensitized oxidation mechanism. In addition, the antioxidant (sodium ascorbate) was able to effectively inhibit the photoproducts formation of dTPT3 and dTPT3 in DNA, suggesting that a reductive environment might protect DNA bearing dTPT3 against UVA oxidation and ameliorate its adverse biological effects. The comprehensive understanding of TPT3' photochemical stability will give researchers helpful guidance to design more photostable UBPs and construct healthier semisynthetic organisms. Abstract : Four photodamage products of dTPT3 have been isolated and identified, which has provided insight into the photodamage mechanism with a Type II photosensitized oxidation. The antioxidant ascorbate was discovered to effectively inhibit the formation of these photodamage products with no new byproducts generated, suggesting that a reductive environment might protect DNA dTPT3 against UVA oxidation and ameliorate its adverse biological effects.